Internalisasi Nilai Humanistik dan Kohesivitas Sosial pada Anak Panti Asuhan Ahbaabul Mukhtar Semarang melalui Kegiatan Berbagi - Anindita Evelyn Jessica Putri; Eneng Nurrahmah; Nadifa Aulia Hafiz; Rahma Awalia Kahfi; Dini Amelia Noviyanti; Gavra Darius Ulul Albab; Andina Nurariana; Halena Azalia Mirabel Firdiyanto; Ika Aulia Khasanah; Muhammad Taufik Hidayat (Pakis Journal Institute, 2026)
This community service program aimed to internalize humanistic values and strengthen social cohesion at Ahbabul Mukhtar Orphanage in Semarang through sharing activities. The implmentation method consisted of several stages, namely observation, coordination, sharing activities, reflection, and evaluation. A humanistic approach was employed, positioning participants as the primary subjects in the learning process. The results demonstrated that sharing activities and direct interactions between the organizing committee and participants contributed to strengthening social cohesion, as evidenced by increased togetherness, empathy, and emotional connectedness among the children. Furthermore, the program successfully fostered humanistic values that positively influenced the participants’ character development. Therefore, this community service initiative proved effective in supporting the psychological and social development of orphanage children. Similar programs are expected to be continuously developed as a sustainable effort to nurture a generation characterized by strong self-confidence, effective communication skills, and a high level of social awareness.